Correlation between cerebrospinal fluid abnormalities before ventriculoperitoneal shunt and postoperative intracranial infection in adult patients with hydrocephalus: A clinical study - Zhang, Huan; He, Xiaozheng; Xie, Linghai; Zhang, Hongbo; Hou, Xusheng; Zhang, Shizhong (Frontiers in Neurology, 2023)
Objective To identify the relationship between preoperative cerebrospinal fluid (CSF) leukocyte, chloride, glucose, aspartate aminotransferase, lactate dehydrogenase, adenosine deaminase, lactic acid and protein levels and ventriculoperitoneal shunt infection. Methods Records of 671 consecutive adult patients who underwent ventriculoperitoneal shunt surgery for the treatment of hydrocephalus at Zhujiang Hospital affiliated with Southern Medical University from January 2011 to March 2022 were reviewed. The patients were divided into infection and non-infection groups based on the presence of postoperative infection. For all patients, we analyzed age; sex; primary disease; preoperative CSF leukocyte, chloride, glucose, aspartate aminotransferase, lactate dehydrogenase, adenosine deaminase, lactic acid and protein levels; postoperative temperature; and postoperative infection. Results A total of 397 patients were included, 28 (7.05%) of whom had an infection within 6 months of the operation and the remaining had no infection. There was no significant difference in age, sex, primary disease, leukocyte, chloride ion, aspartate aminotransferase, lactate dehydrogenase, adenosine deaminase and protein levels in CSF between infection group and non-infection group (p > 0.05). The postoperative infection rate of patients with CSF glucose < 2.8 mmol/L (x2 = 11.650, p = 0.001) and CSF lactic acid >2.8 mmol/L (x2 = 12.455, p < 0.001) was higher than that of patients with CSF glucose level ≥2.8 mmol/L and CSF lactic acid level in the range of (1–2.8) mmol/L, respectively, with statistical difference. Compared with the non-infection group, the level of CSF glucose (t = 4.113, p < 0.001) was significantly lower, and the level of CSF lactic acid (t = 6.651, p < 0.001) was significantly higher in the infection group. Multivariate logistic regression analysis showed that preoperative cerebrospinal fluid glucose < 2.8 mmol/L (OR = 3.911, 95% CI: 1.653~9.253, p = 0.002) and cerebrospinal fluid lactate >2.8 mmol/L (OR = 4.712, 95% CI: 1.892~11.734, p = 0.001) are risk factors for infection after ventriculoperitoneal shunt. ROC analysis revealed that the area under the curve (AUC) for CSF glucose and lactic acid level were 0.602 (95% CI: 0.492–0.713) and 0.818 (95% CI: 0.738–0.898), respectively. The infection group had higher rates of fever and body temperature on postoperative day 3–7 (p < 0.05). Conclusions For adult hydrocephalus patients without clinical manifestations of intracranial infection but only with simple abnormality of cerebrospinal fluid, when the content of glucose in cerebrospinal fluid is < 2.8 mmol/L, and the content of lactic acid is >2.8 mmol/L, it is recommended to perform ventriculoperitoneal shunt after further improvement of cerebrospinal fluid indicators, otherwise, hasty operation will increase the postoperative infection rate. The postoperative fever rate of ventriculoperitoneal shunt surgery is high and the body temperature drops rapidly. If there is still fever after day 3 after surgery, whether there is intracranial infection should be considered.